Examining structural relationships between innovation capability, knowledge sharing, environmental turbulence, and organisational sustainability - Banji Rildwan Olaleye; Joseph Nembo Lekunze; Tsediso Joseph Sekhampu (Cogent Business & Management, 2024)
Businesses that aim to efficiently and effectively combine strategy, governance, and resource allocation face new impediments as the global economy becomes more turbulent. As the environment becomes more demanding and people seek new business opportunities, knowledge sharing helps organizations succeed in the long run. The purpose of this study is to assess the direct structural relationship between variables as well as the moderating influence of environmental turbulence on Nigerian SMEs. This study collected firm-level data from Nigerian manufacturing SMEs via questionnaires, with a sample size of 402. Furthermore, partial least squares structural equation modelling (PLS-SEM) using the SmartPLS software was used to conduct additional analyses. The findings demonstrated a strong correlation between an organization's long-term health and its ability to share knowledge and generate new ideas. They also showed that environmental turbulence affects the connection between the factors that were studied, and this is consistent with previous studies. By considering the presented heuristic model, this study offers valuable insights for managers, researchers, and policymakers to enhance organizational efficiency and sustainability. It adds to the literature on sharing knowledge and innovation in manufacturing SMEs in a turbulence environment.
Keywords: 650; Environmental turbulence; innovation capability; knowledge sharing; organizational sustainability; PLS-SEM; value creation